The Bill of Rights - Nardo, Don, 1947- (San Diego, Calif. : Greenhaven Press, 1998)
Includes an overview of the original debate over the need for a bill of rights, an exploration of some later debates about rights issues, and an appendix of original documents.
Includes bibliographical references (p. 119-124) and index.
Keywords: United States. -- Juvenile literature; United States; Civil rights -- United States -- Juvenile literature; Civil rights